A clinical update on the use of resolute stents with dual anti-platelet therapy interruption. (October 2014) - O'Mahony, Constantinos; Rothman, Martin; Mathur, Anthony
Percutaneous coronary intervention is currently the most commonly used revascularization procedure. This success is a direct consequence of the improved medium- and long-term target vessel patency achieved with drug-eluting stents (DES). However, DES are associated with stent thrombosis (ST), a rare but potentially catastrophic complication. Early interruption of dual anti-platelet therapy (DAPT) is a major risk factor for ST and guidelines recommend a minimum duration of DAPT of 6 to 12 months post implantation. Recently published observational data suggest that premature DAPT interruption is not associated with ST in patients treated with the second-generation Resolute zotarolimus-eluting stent. This article reviews the background to the development of Resolute DES and reviews recently published data on ST and DAPT interruption.